Vitamin D Supplementation in Elderly Black Women Does Not Prevent Bone Loss: A Randomized Controlled Trial. (19th July 2018) - Aloia, John; Fazzari, Melissa; Islam, Shahidul; Mikhail, Mageda; Shieh, Albert; Katumuluwa, Subhashini; Dhaliwal, Ruban; Stolberg, Alexandra; Usera, Gianina; Ragolia, Louis
ABSTRACT: Black Americans have lower levels of serum 25(OH)D but superior bone health compared to white Americans. There is controversy over whether they should be screened for vitamin D deficiency and have higher vitamin D requirements than recommended by the Institute of Medicine (IOM). The purpose of this trial was to determine whether Vitamin D supplementation in elderly black women prevents bone loss. A total of 260 healthy black American women, 60 years of age and older were recruited to take part in a two‐arm, double‐dummy 3‐year randomized controlled trial (RCT) of vitamin D3 versus placebo. The study was conducted in an ambulatory clinical research center. Vitamin D3 dose was adjusted to maintain serum 25(OH)D above 75 nmol/L. Bone mineral density (BMD) and serum were measured for parathyroid hormone (PTH), C‐terminal crosslink telopeptide (CTX), and bone‐specific alkaline phosphatase (BSAP) every 6 months. Baseline serum 25(OH)D3 was 54.8 ± 16.8 nmol/L. There was no group × time interaction effect for any BMD measurement. For all BMD measurements, except for total body and spine, there was a statistically significant negative effect of time ( p < 0.001). An equivalency analysis showed that the treatment group was equivalent to the control group. Serum PTH and BSAP declined, with a greater decline of PTH in the treatment group. The rate of bone loss with serum 25(OH)D above 75 nmol/L is comparable to the rate of loss with serum 25(OH)D at the Recommended Dietary Allowance (RDA) of 50 nmol/L. Black Americans should have the same exposure to vitamin D as white Americans. © 2018 American Society for Bone and Mineral Research.